PENGEMBANGAN GAME ACTION-ADVENTURE BERDASARKAN CERITA RAKYAT SULTAN SURIANSYAH BERMUATAN KEARIFAN LOKAL BANJARMASIN BERBASIS PERANGKAT BERGERAK - Syahidi, Aulia Akhrian; Riyadi, Ahmad; Zakiah, Siti; Astuti, Maya (Jurusan Teknik Komputer, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
Sultan Suriansyah was the King of Bandarmasih (the First King of Banjar) who ruled from 1520-1540 and was the first king to embrace Islam. Tourism-related to the tomb of Sultan Suriansyah is very popular among the people of Banjar. However, the folklore that tells about Sultan Suriansyah is not as popular as his tomb, many young people today don't know it, even across Indonesia it is also not well known for this folklore from South Kalimantan. The purpose of this research is to design and build a folklore game with an action-adventure genre that adapts the story of Sultan Suriansyah to preserve Banjarmasin folklore and as a means to understand grammar in the Banjar language. The research method used is the Game Development Life Cycle with stages in the form of Pre-Production, Production, Testing, and Post-Production. The results show that the game design has been produced in the form of a storyboard and then developed using Godot Engine software with the output of the (.apk) extension application that can be installed on mobile devices. Then the Playtesting and Gameflow testing was also carried out which involved 50 respondents as players with an age range of 13-15 years, the results showed that the games built and tested had met the elements and criteria with an overall average value of 4.84 and no bugs were found in the game. Tests related to player knowledge and justification for using games as a media to preserve folklore and a means to understand the Banjarese language have also been carried out with very good results.